Gold Nanoparticles Reaching New Heights - Rahman, Mohammed; Mohammed Asiri, Abdullah (IntechOpen, 2019)
Gold Nanoparticles - Reaching New Heights contains recent research on the preparation, characterization, fabrication, and potential of optical and biological applications of gold nanoparticles (AuNPs). It is promising novel research that has received a lot of interest over the last few decades. It covers advanced topics on optical, physical, medicinal, and biological applications of AuNPs. Development of green nanotechnology is generating the interest of researchers towards the synthesis of eco-friendly, safe, non-toxic applications, which can be used for manufacture at a large scale. These are simple, cost-effective, stable, enduring, and reproducible aqueous room temperature synthesis applications to obtain the self-assembly of AuNPs. This potentially unique work offers various approaches to R&D with AuNP materials in aqueous or non-aqueous phases through fully modified or unmodified states as hybrids. Nanotechnology and nanoscience can regulate substances at the nanoscale, and nanodimension substances of a few nanometers allow us to control the novel practical applications of AuNPs. This book presents an overview of current AuNP fundamental and substantial applications and research worldwide, which investigates the techniques of AuNP preparation, various types of characterization, and possible applications related to AuNP research. It is an important book for research organizations, government research centers, academic libraries, and R&D groups interested in recent research and development of AuNPs.